Prototype Fault Current Limiter Using Transformer and a Modular Device of YBCO Coated Conductor - Baldan, C. A. [UNESP]; Lamas, J. S.; Bernardes, A. A.; Shigue, C. Y.; Ruppert Filho, E. (Springer, 2013)
A superconducting fault current limiter (SCFL) consisted of a transformer with low reactance connected to the power line and with the secondary winding short-circuited by a modular superconducting limiter device with 16 elements connected in series was constructed and tested. The designed coupling transformer has low dispersion reactance in order to limit the voltage drop in the power line within the range of 5 % to 10 %. The experimental results showed that an insertion of a 0.125 Omega resistance limited the peak current to a factor of 2.5 times of the unlimited current. The power dissipation reached 39 kW during 100 ms, with an energy density of 380 J/cm(3). Based on these results, the SCFL will be further tested in a 3 MVA (15 kV/380 V) generator for currents up to 10 kA.
Keywords: Superconducting fault current limiter; YBCO coated conductor; YBCO recovery characteristics; Current limiting ratio